Template-free hierarchical trimetallic oxide photocatalyst derived from organically modified ZnCuCo layered double hydroxide - Gholami, Peyman; Khataee, Alireza; Ritala, Mikko (Elsevier Sci Ltd, 2022)
High-performance photocatalysts have considerable potential to address energy and environmental issues. In this study, dodecylbenzenesulfonate (DBS) modified ZnCuCo layered double hydroxide (DBS-ZnCuCo LDH) microspheres were synthesized through the facile template-free hydrothermal method. Subsequently, ZnCuCo mixedmetal oxides (MMOs) with morphological features of the DBS modified LDH, enhanced surface area, increased light absorption and effective charge separation were prepared by the calcination of the as-synthesized LDH at 650 degrees C. Structural, morphological, and photoelectrochemical properties of ZnCuCo and DBS-ZnCuCo LDHs and the corresponding MMOs (ZnCuCo MMO1 and ZnCuCo MMO2) were investigated. SEM and TEM images revealed that DBS-ZnCuCo LDH and ZnCuCo MMO2 possess 3D flower-like hierarchical morphologies with interlaced petal-like nanosheets. Although ZnCuCo LDH was inactive for photocatalytic H-2 production under visible light irradiation, ZnCuCo MMO2 exhibited a high H2 production rate (3700 mu mol g(-1) h(-1)), benefiting from the synergy of the ZnO, CuO, and Co3O4. Furthermore, 95% sulfamethazine (SMZ) degradation was obtained after 60 min of photocatalysis, which is considerably higher than the degradation efficiency of ZnCuCo LDH (24%) and ZnCuCo MMO1 (58%). Based on the photoelectrochemical tests, Z-scheme and double charge transfer mechanisms were proposed to explain the enhanced photocatalytic H-2 production and degradation of SMZ. Scavenging tests revealed that O-2(center dot-) radicals were the main reactive species in the photodegradation of SMZ. A possible degradation pathway was proposed based on the detection of intermediate products.
Keywords: Trimetallic oxide; Dodecylbenzenesulfonate; Hydrogen evolution; Photocatalysis; Antibiotics degradation